2022
DOI: 10.1177/15480518211062563
|View full text |Cite
|
Sign up to set email alerts
|

Walking Our Evidence-Based Talk: The Case of Leadership Development in Business Schools

Abstract: Academics have lamented that practitioners do not always adopt scientific evidence in practice, yet while academics preach evidence-based management (EBM), they do not always practice it. This paper extends prior literature on difficulties to engage in EBM with insights from behavioral integrity (i.e., the study of what makes individuals and collectives walk their talk). We focus on leader development, widely used but often critiqued for lacking evidence. Analyzing 60 interviews with academic directors of lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 95 publications
0
9
0
2
Order By: Relevance
“…Yet, Reyes et al (2019) concluded from their analysis of these higher educational leadership development efforts that, "in practice, LD programs generally use approaches that are convenient and inexpensive rather than rooted in science" (p. 10). Leroy et al, (2022) expanded this research by conducting a more comprehensive analysis of 60 business schools around the globe, concluding that evidence-based leadership development is not widely accepted nor produced by these schools. Indeed, there was very little evidence that demonstrated there was even a collective consensus associated with what constitutes effective leadership development, as one should expect from professional schools.…”
Section: Challenging What Constitutes Leadership Development and Prop...mentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, Reyes et al (2019) concluded from their analysis of these higher educational leadership development efforts that, "in practice, LD programs generally use approaches that are convenient and inexpensive rather than rooted in science" (p. 10). Leroy et al, (2022) expanded this research by conducting a more comprehensive analysis of 60 business schools around the globe, concluding that evidence-based leadership development is not widely accepted nor produced by these schools. Indeed, there was very little evidence that demonstrated there was even a collective consensus associated with what constitutes effective leadership development, as one should expect from professional schools.…”
Section: Challenging What Constitutes Leadership Development and Prop...mentioning
confidence: 99%
“…We now call for leadership research to move above the individual level of analysis in determining the effectiveness of leadership development interventions. For example, in an article by Leroy et al, (2022) published in this journal, the authors researched common declarations associated with most business school missions around the globe regarding their development of future leaders (Day & Dragoni, 2015;Reyes, et al 2019). They reported that "a content analysis of twenty-first century mission statements of top business schools indicates that the majority sees leader development as critical (Kniffin et al 2020)," (p. 6), and that these business schools serve a critical role in developing the next formation of organizational and societal leaders.…”
Section: Challenging What Constitutes Leadership Development and Prop...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kepemimpinan atau leadership dan globalisasi berkaitan dengan antisipasi terhadap kecenderungan-kecenderungan yang terjadi pada masa mendatang, memberi inspirasi kepada setiap orang luntuk mengetahui dan memahami kemungkinan adanya visi baru (Rommel et al, 2021). Jiwa kepemimpinan adalah suatu sifat yang dianugerahkan Tuhan kepada setiap insan yang tidak semua manusia memiliki sifat tersebut (Leroy et al, 2022), yakni sifat seseorang yang dapat mengendalikan atau mengatur seseorang atau sekelompok manusia dalam sebuah organisasi, seperti: sekolah, tempat kerja, keluarga, dan lain sebagainya. Leadership merupakan bagian dari softskill atau kemampuan seseorang dalam berhubungan dengan orang lain (interpersonal skill) serta kemampuan dalam mengatur atau mengendalikan dirinya sendiri.…”
Section: Pendahuluanunclassified
“…Furthermore, this theory relates to organizational performance and its relationship to different factors that support organizational performance. In this regard, more emphasis on the organization would be to be supported with different variables that are dynamic and changeable from business to business (Leroy et al, 2022). However, it is also noted that this theory was widely used in different studies that were considered adequate for developing the theoretical frameworks of those studies.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%